Syntheses, crystal-solution structures and magnetic properties of a series of decanuclear heterometallic [LnIII2CoII4CoIII4] (Ln = Eu, Gd, Tb, Dy) clusters. Issue 30 (13th July 2018) - Yu, You-Zhu; Hu, Yue-Qiao; Guo, Yu-Hua; Niu, Yong-Sheng; Yang, Li-Guo; Song, Hai-Xiang; Shen, Yan-Hong; Zheng, Xiao-Ming; Hou, Shao-Gang; Feng, Guo-Dong
Abstract : Four unprecedented decanuclear heterometallic [Ln2 Co8 ] clusters based on a diethanolamine ligand were synthesized through a facile solution method. Abstract : Four unprecedented decanuclear heterometallic [Ln2 CoII4CoIII4] clusters based on a diethanolamine ligand (H2 dea), namely [Eu2 CoII4CoIII4(dea)8 (HCOO)4 (OH)2 (Cl)2 (CH3 OH)2 ]Cl2 ·4CH3 OH·2H2 O (1 ), [Gd2 CoII4CoIII4(dea)8 (HCOO)4 (OH)2 (Cl)2 (CH3 OH)2 ]Cl2 ·4CH3 OH·2H2 O (2 ), [Tb2 CoII4CoIII4(dea)8 (HCOO)4 (OH)2 (Cl)2 (CH3 OH)2 ]Cl2 ·2CH3 OH·4H2 O (3 ) and [Dy2 CoII4CoIII4(dea)8 (HCOO)4 (OH)2 (Cl)2 (CH3 OH)2 ]Cl2 ·2CH3 OH·4H2 O (4 ) were synthesized through a facile solution method. Single-crystal X-ray diffraction analyses reveal that complexes1–4 consist of a [Ln2 CoII4CoIII4] core, which is constructed by bridging a quasi-double cuboidal [Ln2 CoII2CoIII2] core with two [Co II Co III ] units. Electrospray ionization mass spectrometry (ESI-MS) using methanol solution reveals that complexes1–4 are stable in the solution, and the clusters undergo three different substitution reactions (Cl − replaced by OH −, OH − replaced by CH3 O − and HCOO − replaced by OH − /CH3 O − ) at the same time in the ionization state. Magnetic susceptibilities reveal ferromagnetic couplings within complexes3 and4, and the magnetocaloric effect (MCE) for2 was also evaluated and the maximum entropy change (−Δ S m ) value reaches 16.3 J kg −1 K −1 at about 3 K and 5 T.